48 ANALISA PENGARUH ENDORSER TERHADAP BRAND EQUITY YANG BERDAMPAK PADA PROSES PURCHASE INTENTION KONSUMEN ONLINE SHOP - Yanuar; Yusuf Muchtar; Nur Aida (Jurnal Ekonomi Bisnis Indonesia, 2021)
The purpose of this study was to determine the effect of celebrity endorsers on brand equity, brand equity on purchase intentions, celebrity endorsers on purchase intentions, and Celebrity Endorser on Brand Equity that have an impact on Purchase Intention. This study used 100 respondents online shop, using path analysis method. Data processing tools use SPSS 22.0. The results showed that Celebrity Endorser had a significant influence on consumers' online shop brand equity. Celebrity Endorser has a significant influence on Purchase Intention of online shop consumers. Brand Equity has an influence on Purchase Intention of online shop consumers and Celebrity Endorser has a significant influence on Brand Equity which has a positive impact on Purchase Intention of online shop consumers.